Respuesta :
Answer:
-5x+5
Step-by-step explanation:
(6x-3)-(11x-8)=
6x-11x-3+8=
-5x+5
The subtraction of (6x -3) - (11x - 8) is 5(x - 1)
The subtraction method of algebraic terms takes a process whereby you first open the brackets, followed by rearranging variables with common-like terms.
Given that:
(6x -3) - (11x - 8)
Open brackets
= 6x - 3 - 11x + 8
Collecting like terms by rearrangement
= 6x - 11x - 3 + 8
= -5x + 5
Multiply through by (-)
= 5x - 5
Factorize out (5)
= 5(x - 1)
Therefore, we can conclude that the subtraction of (6x -3) - (11x - 8) is 5(x - 1)
Learn more about subtraction here:
https://brainly.com/question/20671719?referrer=searchResults